2015
DOI: 10.1016/j.ijlcj.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Prescription fraud: A comparison of pharmacists' and laypersons' perceptions of suspicious prescription presentation behaviour

Abstract: Australia has seen an increase in the abuse of prescription drugs, including obtaining them through prescription fraud. As the gate-keepers to medications, pharmacists have the opportunity to assess the veracity of prescriptions and those presenting them. The present study investigated how pharmacists detect deception in the context of prescription fraud, and whether their experience affects their levels of suspicion compared with non-experienced laypersons. An online survey was completed by 43 pharmacists and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In conclusion, the study proposed measures and policies that can safeguard the public from the danger of counterfeit drugs. McCarthy and Porter (2015) observed that Australia has seen an increase in the abuse of prescription drugs, including obtaining them through prescription fraud. As the gatekeepers to medications, pharmacists have the opportunity to assess the veracity of prescriptions and those presenting them.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%
“…In conclusion, the study proposed measures and policies that can safeguard the public from the danger of counterfeit drugs. McCarthy and Porter (2015) observed that Australia has seen an increase in the abuse of prescription drugs, including obtaining them through prescription fraud. As the gatekeepers to medications, pharmacists have the opportunity to assess the veracity of prescriptions and those presenting them.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%